Renal function is a major predictor of circulating acyl-CoA-binding protein/diazepam-binding inhibitor - Schürfeld, Robin; Sandner, Benjamin; Hoffmann, Annett; Klöting, Nora; Baratashvili, Ekaterine; Nowicki, Marcin; Paeschke, Sabine; Kosacka, Joanna; Kralisch, Susan; Bachmann, Anette; Frille, Armin; Dietel, Anja; et al. (Frontiers in Endocrinology, 2023)
Objective: Acyl-CoA-binding protein (ACBP)/diazepam-binding inhibitor has lately been described as an endocrine factor affecting food intake and lipid metabolism. ACBP is dysregulated in catabolic/malnutrition states like sepsis or systemic inflammation. However, regulation of ACBP has not been investigated in conditions with impaired kidney function, so far. Design/Methods: Serum ACBP concentrations were investigated by enzyme-linked immunosorbent assay i) in a cohort of 60 individuals with kidney failure (KF) on chronic haemodialysis and compared to 60 individuals with a preserved kidney function; and ii) in a human model of acute kidney dysfunction (AKD). In addition, mACBP mRNA expression was assessed in two CKD mouse models and in two distinct groups of non-CKD mice. Further, mRNA expression of mACBP was measured in vitro in isolated, differentiated mouse adipocytes - brown and white - after exposure to the uremic agent indoxyl sulfate. Results: Median [interquartile range] serum ACBP was almost 20-fold increased in KF (514.0 [339.3] µg/l) compared to subjects without KF (26.1 [39.1] µg/l) (p<0.001). eGFR was the most important, inverse predictor of circulating ACBP in multivariate analysis (standardized β=-0.839; p<0.001). Furthermore, AKD increased ACBP concentrations almost 3-fold (p<0.001). Increased ACBP levels were not caused by augmented mACBP mRNA expression in different tissues of CKD mice in vivo or in indoxyl sulfate-treated adipocytes in vitro. Conclusions: Circulating ACBP inversely associates with renal function, most likely through renal retention of the cytokine. Future studies need to investigate ACBP physiology in malnutrition-related disease states, such as CKD, and to adjust for markers of renal function.